GSK2878175, a pan‐genotypic non‐nucleoside NS5B polymerase inhibitor, in healthy and treatment‐naïve chronic hepatitis C subjects. Issue 1 (3rd August 2017) - Gardner, S. D.; Kim, J.; Baptiste‐Brown, S.; Lopez, V.; Hamatake, R.; Gan, J.; Edwards, S.; Elko‐Simms, L.; Dumont, E. F.; Leivers, M.; Hong, Z.; Paff, M. T.
Summary: GSK2878175 is a potent, pan‐genotypic, non‐nucleoside, nonstructural protein 5B palm polymerase inhibitor being developed for the treatment of chronic hepatitis C (CHC). A first‐in‐human, randomized, placebo‐controlled, dose escalation study, evaluated the safety and pharmacokinetics of GSK2878175 administered as single and repeat oral doses (once daily for 14 days) to healthy volunteers. A separate proof‐of‐concept, placebo‐controlled, repeat dose (once daily for 2 days) study evaluated the safety, pharmacokinetics and antiviral activity of GSK2878175 monotherapy in treatment‐naïve, noncirrhotic, subjects with hepatitis C virus (HCV) genotype 1 [1a and 1b], 2, or 3. No deaths or SAEs were reported in either study, and treatment was well‐tolerated. Across all the HCV genotypes, GSK2878175 monotherapy at doses of 10, 30 or 60 mg once daily for 2 days produced a statistically significant multilog reduction ( P <.001) in plasma HCV RNA log10 IU/mL from Baseline to 24, 48 and 72 hours after the first dose of GSK2878175 compared to placebo. The reduction in HCV RNA was sustained for a prolonged period across all of the active treatment groups, consistent with the long apparent half‐life of GSK2878175 that was observed (mean t1/2 range: 60‐63 hours in the CHC subjects). In summary, GSK2878175, when administered to healthy subjects and subjects with CHC, did not reveal any safety concerns that would limit or preclude further clinical development. GSK2878175 monotherapy across a wide dose range produced substantial reduction in HCV RNA, irrespective of HCV genotype. The results from these studies support further evaluation of GSK2878175‐based regimens.